Influence of outer rail rising of railway curve on critical speed at which trains can still pass curve without leaving the track - Mokin, O. B.; Mokin, B. I. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Taking into account the effect of outer rail raising there had been created the mathematical model for the critical speed at which trains can still pass railway curve without leaving the rails of the track.